INTERLEUKIN-17A IS A NEW TARGET OF ANTICYTOKINE THERAPY FOR ANKYLOSING SPONDYLITIS - Sh. F. Erdes (Научно-практическая ревматология, 2016)
Therapy for ankylosing spondylitis (AS) is a challenge for a physician, primarily because of a small number of therapeutic alternatives. Interleukin-17 (IL17), a novel promising therapeutic  target, has been recently disclosed. The first representative of the new group of drugs – anti-IL17A monoclonal  antibodies (secukinumab)  has emerged, which allows expanding therapeutic  opportunities  for this disease. Trials have shown that secukinumab is effective in treating AS, has low immunogenicity and its safety profile does not virtually differ from that of placebo.